Optimalisasi Media Sosial sebagai Ruang Diskusi Teologi Publik: Strategi Peningkatan Keterampilan Literasi Digital bagi Pendidik Kristen dalam Menghadapi Post-Truth - Ipan Morris Panggaribuan; Subekti, Tri (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
The post-truth era and the dominance of social media pose significant challenges to public theological discussion practices, making the Christian community vulnerable to the spread of misinformation. This study aims to develop and test a digital literacy model for Christian educators to optimize social media as a space for healthy and critical dialogue. Using a mixed-method sequential explanatory approach, the study shows a significant improvement in information verification capacity and algorithmic awareness after the intervention. Qualitative findings reveal a paradox between emotional engagement and critical awareness, which was successfully addressed through the internalization of Christian communication ethics. The integrated model, which combines technical skills, public theology, and ethics, proves effective in transforming educators from passive consumers to active change agents in the digital space. Thus, educators can ethically and responsibly moderate theological discourse, making a significant contribution to creating a more thoughtful and open digital space for deeper and more meaningful theological dialogue. This research has implications for the development of digital literacy curricula in Christian education and serves as an initial step toward shaping a generation of educators who are critical and intelligent in facing the digital challenges of the future.